2019
DOI: 10.1108/lhs-09-2018-0044
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate leadership in palliative and end-of-life care: a focus group study

Abstract: Purpose The purpose of this study was to explore compassionate leadership with those involved in leading system-wide end-of-life care. Its purpose was to: define compassionate leadership in the context of palliative and end-of-life care; collect accounts of compassionate leadership activity from key stakeholders in end-of-life and palliative care; and identify examples of compassionate leadership in practice. Design/methodology/approach Four focus groups involving staff from a range of healthcare organisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 46 publications
0
51
0
1
Order By: Relevance
“…Compassionate leadership can have a positive impact on practice (Hewison et al, 2018(Hewison et al, , 2019 and MacArthur et al (2017) contend there is need for a strategic vision for compassionate care that recognises and values the role of relationships and invests in practice development and leadership at all levels, although they concede that the organisational infrastructure necessary to embed and sustain compassionate care amidst all the other health service pressures and priorities, is less clear. In contrast, there is evidence about what is required to construct compassionate leadership: organisations that have inspiring visions operationalised at every level; with clear, aligned objectives for all teams, departments and individual staff; supportive and enabling people management and high levels of staff engagement; learning, innovation and quality improvement embedded in the practice of all staff; and effective team working (West et al, 2015).…”
Section: Compassionate Leadership and Clinical Professionsmentioning
confidence: 99%
“…Compassionate leadership can have a positive impact on practice (Hewison et al, 2018(Hewison et al, , 2019 and MacArthur et al (2017) contend there is need for a strategic vision for compassionate care that recognises and values the role of relationships and invests in practice development and leadership at all levels, although they concede that the organisational infrastructure necessary to embed and sustain compassionate care amidst all the other health service pressures and priorities, is less clear. In contrast, there is evidence about what is required to construct compassionate leadership: organisations that have inspiring visions operationalised at every level; with clear, aligned objectives for all teams, departments and individual staff; supportive and enabling people management and high levels of staff engagement; learning, innovation and quality improvement embedded in the practice of all staff; and effective team working (West et al, 2015).…”
Section: Compassionate Leadership and Clinical Professionsmentioning
confidence: 99%
“…The observation of the experience of others through the surrogate experience could increase the confidence of an individual [24]. Another study [25] showed that self-efficacy in end-of-life care was strengthened by providing information that senior nurses were able to collaborate effectively with medical staff or families.…”
Section: Discussionmentioning
confidence: 99%
“…However, the benefits of trust go beyond increasing synergy among collaborators, which ostensibly leads to better team performance. However, resilience is far too often conceptualized as an individual capacity (Aburn et al, 2020), placing responsibility for well-being on the stressed-out worker, who might be encouraged to call an organizational help line (Hewison et al, 2019) or meditate and do some yoga. Therefore, we propose resilience must be conceived both as collective (i.e., team resilience) and as something that emerges from and is sustained by compassionate collaborative interaction.…”
Section: Relationality and Team Carementioning
confidence: 99%